101 life hacks : genius ways to simplify your world - Andrus, Aubre (National Geographic kids., 2020)
Compiles 101 practical tips, techniques, tricks, and solutions for real-life problems, along with the science behind why they work. Also profiles the scientists and inventors who created the life hacks, and includes color photographs.